Humanization with CD34-positive hematopoietic stem cells in NOG-EXL mice results in improved long-term survival and less severe myeloid cell hyperactivation phenotype relative to NSG-SGM3 mice - Willis, Elinor; Verrelle, Jillian; Banerjee, Esha; Assenmacher, Charles-Antoine; Tarrant, James C; Skuli, Nicholas; Jacobson, Moriah L; O'Rouke, Donald M; Binder, Zev A; Radaelli, Enrico (Veterinary pathology, 2024)
NSG-SGM3 and NOG-EXL mice combine severe immunodeficiency with transgenic expression of human myeloid stimulatory cytokines, resulting in marked expansion of myeloid populations upon humanization with CD34+ hematopoietic stem cells (HSCs). Humanized NSG-SGM3 mice typically develop a lethal macrophage activation syndrome and mast cell hyperplasia that limit their use in long-term studies (e.g., humanization followed by tumor xenotransplantation). It is currently unclear to what extent humanized NOG-EXL mice suffer from the same condition observed in humanized NSG-SGM3 mice. We compared the effects of human CD34+ HSC engraftment in these two strains in an orthotopic patient-derived glioblastoma model. NSG-SGM3 mice humanized in-house were compared to NOG-EXL mice humanized in-house and commercially available humanized NOG-EXL mice. Mice were euthanized at humane or study endpoints, and complete pathological assessments were performed. A semiquantitative multiparametric clinicopathological scoring system was developed to characterize chimeric myeloid cell hyperactivation (MCH) syndrome. NSG-SGM3 mice were euthanized at 16 weeks after humanization because of severe deterioration of clinical conditions. Humanized NOG-EXL mice survived to the study endpoint at 22 weeks after humanization and showed less-severe MCH phenotypes than NSG-SGM3 mice. Major differences included the lack of mast cell expansion and limited tissue/organ involvement in NOG-EXL mice compared to NSG-SGM3 mice. Engraftment of human lymphocytes, assessed by immunohistochemistry, was similar in the two strains. The longer survival and decreased MCH phenotype severity in NOG-EXL mice enabled their use in a tumor xenotransplantation study. The NOG-EXL model is better suited than the NSG-SGM3 model for immuno-oncology studies requiring long-term survival after humanization.